A mentoring program drills down on the Common Core. (March 2015) - Davis, Emily; Sinclair, Steve; Gschwend, Laura
The Santa Cruz/Silicon Valley New Teacher Project – under the aegis of the New Teacher Center – devised a program to train teacher mentors to help new teachers incorporate the Common Core standards into their teaching. The three-year program yielded five critical lessons: Mentors need ongoing support to develop their readiness and willingness to guide new teachers in implementing the Common Core; mentors need to be grand generalists of the Common Core so they can work with teachers in many contexts; rolling out the Common Core requires leveraging resources and relationships in new ways; working with new teachers is a balancing act; and mentors and new teachers can quickly become Common Core leaders.